FTIR and EDXRF Investigations of Salt Tolerant Soybean Mutants - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL; ATAK, ÇİMEN; ÇELİK, ÖZGE (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
Molecular structure and elemental composition of soybean (Glycine max L. Merr.) seeds of S04-05 (Ustun-1) variety together with its salt tolerant mutants were investigated by Fourier transform infrared (FTIR) and energy dispersive X-ray fluorescence (EDXRF) spectrometry. Salt tolerant soybean mutants were in vivo and in vitro selected from the M-2 generation of gamma irradiated S04-05 soybean variety. Examination of the secondary structure of proteins revealed the presence of some alterations in soybean mutants in comparison to those of the control groups. The difference IR spectra indicated that salt tolerant mutants (M-2) have less protein but more lipid contents. Chemometric treatment of the FTIR data was performed and principle component analysis (PCA) revealed clear difference between control group of seeds and mutants. EDXRF analysis showed that salt tolerant mutants considerably contained more chlorine, copper and zinc elements when compared to the control group, although most of the trace elements concentrations were not significantly altered. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: EDXRF; IR Spectroscopy; Gamma-irradiated Seeds; Soybean; Salt Tolerant Mutants; Protein Secondary Structure; Desiccation Tolerance; Somatic Embryos; Plant; Spectroscopy; Stability; Matrix; Pollen; Seeds; Films; IR Spektroskopisi; Gama Işınlarına Tabi Tutulmuş Tohumlar; Soya Fasulyesi; Tuza Dayanıklı Mutantlar; Protein İkincil Yapısı; Kurutulma Toleransı; Somatik Embriyolar; Bitki; İstikrar; Matris; Polen; Tohumlar; Filmler